2017
DOI: 10.1089/dna.2016.3425
|View full text |Cite
|
Sign up to set email alerts
|

“Cell Migration” Is the Ontology Group Differentially Expressed in Porcine Oocytes Before and After In Vitro Maturation: A Microarray Approach

Abstract: Maturation of cumulus-oocyte complexes (COCs) is crucial for further successful monospermic fertilization, embryo growth, and implantation. All these events are accompanied by proliferation and differentiation of cumulus cells. The migration of COCs to the oviduct after ovulation and the interaction between female gametes and/or embryos with maternal tissues are still poorly recognized on the molecular level. This study was aimed to first demonstrate the mRNA expression profile of cell migration markers during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Moreover it was defined that proper regulation of these processes is required for complete maturation of oocytes. Our previous studies have shown various aspects of changes occurring in oocytes during maturation [1][2][3] and impact of environmental changes on these processes [4][5]. Morphological and biochemical alterations associated with the ability of embryo to formation of blood vessels networks seem to play pivotal role in successful implantation, decidualization and early embryo -maternal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it was defined that proper regulation of these processes is required for complete maturation of oocytes. Our previous studies have shown various aspects of changes occurring in oocytes during maturation [1][2][3] and impact of environmental changes on these processes [4][5]. Morphological and biochemical alterations associated with the ability of embryo to formation of blood vessels networks seem to play pivotal role in successful implantation, decidualization and early embryo -maternal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro culture (IVC) systems are applied to mimic in vivo conditions, the proportion of fully mature and fertilizable oocytes after IVC in numerous mammalian species is still unsatisfactory [28]. Recently, several studies aimed to find new molecular markers of oocyte maturation ability in order to improve IVC models and increase the number of fully mature gametes [2933]. Therefore, in this study we performed gene expression analysis in porcine oocytes before and after IVM in order to define new molecular markers of female gamete maturation capability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we introduced the primary culture systems based on: (1) human ovarian granulosa cells, (2) porcine ovarian granulosa cells, (3) porcine endometrial and myometrial cells, and (4) porcine epithelial oviductal cells (OECs) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%